An Analysis of Students’ Writing Ability in Narrative Texts at the SMA N 4 Tanjungpinang - Nurfadilah Nurfadilah; Nana Raihana Askurny; Rara Cahya Aprilya; Nurul Atiqah Rizwana; Melisa Hazana; Elina Bayusri (Perkumpulan Dosen Muslim Indonesia - Sulawesi Selatan, 2025)
This study aims to describe students' ability in writing narrative texts and identify common mistakes that are often found in their writing. This study used a descriptive quantitative approach with 31 students of class 11.1 SMA Negeri 4 Tanjungpinang as the subjects. Data were collected through narrative text writing assignments and analyzed using an assessment rubric based on five aspects: content, organization, grammar, vocabulary, and mechanics. The results showed that 16% of students had excellent writing ability, 45% were in the good category, and 39% were fair. The most dominant mistakes were found in the aspects of grammar and mechanics, such as inappropriate use of tenses, punctuation and spelling mistakes. Meanwhile, the content and organization aspects showed better results, indicating that most students were able to understand the basic structure of the narrative text. This finding is expected to provide an illustration for teachers to focus more on improving students' grammar and mechanics aspects in learning to write.